Analisis Diferensial Dalam Pengambilan Keputusan Menerima atau Menolak Pesanan Khusus (Studi Kasus pada UMKM Keripik Singkong Sedulur) - Selfi Nurul Fadilah; Neneng Dahtiah (Indonesian Accounting Literacy Journal, 2023)
Decision making is one of the activities that often occurs in business, including small businesses such as UMKM. In the decision-making process, the costs and benefits of one alternative must be compared with the costs and benefits of other alternatives. Costs that differ among the various available alternatives are called differential costs. UMKM Sedulur Cassava Chips is a business in the food sector by producing cassava chips. In its operations, these UMKM have received and are still being offered special orders to utilize half of the company's idle production capacity. However, until now the company has not dared to decide to accept the special order again due to several reasons, one of which is the company does not know whether accepting the special order will benefit the company or not. Using the case study research method, the authors analyze the differential costs, revenues and profits of the company when it accepts and rejects special orders as a consideration for the company in making decisions to accept special orders in the future. The results of the study illustrate that when receiving special orders the company will experience an increase in revenue of Rp. 4,860,000 and an increase in production costs of Rp. 3,948,500 so that there will be an increase in profits of Rp. 911,500. With so the authors suggest to accept the special order.